Soliciting additional concerns in the primary care consultation and the utility of a brief communication intervention to aid solicitation: A qualitative study. Issue 5 (May 2016) - Summers, Rachael H.; Moore, Michael; Ekberg, Stuart; Chew-Graham, Carolyn A.; Little, Paul; Stevenson, Fiona; Brindle, Lucy; Leydon, Geraldine M.
Highlights: GPs report benefits of soliciting additional concerns early in consultations. Benefits include enhanced time management and potential to increase patient satisfaction. Challenges include soliciting sensitive concerns prior to establishing rapport. Interventions to support soliciting concerns may enhance consultation efficiency. Abstract: Objective: To investigate the perspectives of general practitioners (GPs) on the practice of soliciting additional concerns (ACs) and the acceptability and utility of two brief interventions (prompts) designed to aid the solicitation. Methods: Eighteen GPs participating in a feasibility randomised controlled trial were interviewed. Interviews were semi-structured and audio-recorded. Data were analysed using a Framework Approach. Results: Participants perceived eliciting ACs as important for: reducing the need for multiple visits, identifying serious illness early, and increasing patient and GP satisfaction. GPs found the prompts easy to use and some continued their use after the study had ended to aid time management. Others noted similarities between the intervention and their usual practice. Nevertheless, soliciting ACs in every consultation was not unanimously supported. Conclusion: The prompts were acceptable to GPs within a trial context, but there was disagreement as to whether ACs should be solicited routinely. Some GPs considered the intervention to aid their prioritisation efficiency within consultations. Practice implications: Some GPs will find prompts which encourage ACs to be solicited early in the consultation enable them to better organise priorities and manage time-limited consultations more effectively.